An analysis into the implementation of Broad Based Black Economic Empowerment (BBBEE) in Namibia : selected case studies - Teek, Pia Mbemurukira (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPA (Public Management and Planning))--University of Stellenbosch, 2009.